Sovremennaâ âzykovaâ situaciâ. Tendencii razvitiâ russkogo literaturnogo âzyka - Solganik, Grigorij Â. (Stylistyka, 2020)
The article is dedicated to an analysis o f the modem Russian language ‘situation’. The main factors influencing the development of standard Russian are analyzed. First among these factors is media language. The perspectives ou the development o f modem Russian are characterized.